Process monitoring through manifold regularization-based GMM with global/local information. (September 2016) - Yu, Jianbo
Graphical abstract: Highlights: A novel manifold learning algorithm is proposed for complicated process control. Gaussian mixture model with manifold regularization is developed for process modeling. A probabilistic indicator is developed for quantifying process states. The results illustrate the potential application of the proposed process monitoring system. Abstract: The nonlinear and multimodal characteristics in many manufacturing processes have posed some difficulties to regular multivariate statistical process control (MSPC) (e.g., principal component analysis (PCA)-based monitoring method) because a fundamental assumption is that the process data follow unimodal and Gaussian distribution. To explicitly address these important data distribution characteristics in some complicated processes, a novel manifold learning algorithm, joint local intrinsic and global/local variance preserving projection (JLGLPP) is proposed for information extraction from process data. Based on the features extracted by JLGLPP, local/nonlocal manifold regularization-based Gaussian mixture model (LNGMM) is proposed to estimate process data distributions with nonlinear and multimodal characteristics. A probabilistic indicator for quantifying process states is further developed, which effectively combines local and global information extracted from a baseline GMM. Thus, the JLGLPP and LNGMM-based monitoring model can be used effectively for online process monitoring under complicated working conditions. The experimental results illustrate that the proposed method effectively captures meaningful information hidden in the process signals and shows superior process monitoring performance compared to regular monitoring methods.